Third‐generation Sulfite Biosensor Based on Sulfite Oxidase Immobilized on Aminopropyltriethoxysilane Modified Indium Tin Oxide. Issue 1 (25th October 2016) - Saengdee, Pawasuth; Promptmas, Chamras; Zeng, Ting; Leimkühler, Silke; Wollenberger, Ulla
Abstract: In this paper we report a sulfite biosensor based on immobilization and bioelectrocatalysis of human sulfite oxidase ( h SO) on indium tin oxide (ITO). Stable immobilization of catalytically active enzyme in a direct electron transfer configuration was achieved after modification of ITO with aminopropyltriethoxysilane (APTES). The electrochemical characteristics of the h SO modified electrode have been investigated by cyclic voltammetry for various pretreatment and binding conditions. Amperometry was utilized to demonstrate the current responses of the sulfite sensor toward sodium sulfite in an aqueous solution under the optimized conditions. The proposed sulfite sensor exhibits a fast response and high sulfite sensitivity with a linear range of 0.5 to 2 μM. An additional polyvinyl alcohol (PVA) cover membrane was applied to extend the linear working range. As a result, the upper concentration in the linear range for the sulfite sensor was extended from 2 μM to 20 μM for 5 % PVA. In addition, the sulfite sensor with PVA has improved storage stability when kept in 0.5 mM Tris‐buffer, pH 7.0 at 4 °C. Abstract :